Populismo y política exterior: India hacia Israel - Verspecht , Erika Alitzel; Tawil, Marta (El Colegio de México A.C., 2022)
In this article, we identify the elements of a populist foreign policy strategy by analyzing the relations between India and Israel since Narendra Modi became prime minister in 2014. We argue that a foreign policy strategy is populist when: 1) it appeals to the will of the people; 2) it accentuates the confrontation between elites and otherness, and the people in speech; 3) decisions are centralized; it intends to portray congruence between the actions and the national role conception, which legitimizes those decisions. Moreover, we claim that a populist strategy in foreign policy is constructed from complex calculations that must foresee national and international pressures.